2011
DOI: 10.1088/1742-6596/305/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of corrosion damaged prestressed concrete joists: the Pescara Benchmark

Abstract: An experimental campaign named the Pescara benchmark and devoted to study the dynamic behaviour of corroded p.c. joists has been conducted. The steel corrosion reduces the area of the reinforcement and causes cracking of concrete so that r/c members are subjected to loss of strength and stiffness. It is of interest to evaluate the corrosion level at which the damage can be detected through signal processing procedures and how close such level is to the r/c member safety limits. Joists of current industrial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Due to the closing of the cracks caused by the prestressing, only slight changes of the modal frequencies were detected before the yielding of reinforcement. Similar conclusions are reported in the works by Capozucca [10] and Di Evangelista et al [11]. Negligible variations of modal frequencies are also reported in [12] for beams prestressed by external tendons and tested with impact hammer tests.…”
Section: Introductionsupporting
confidence: 89%
“…Due to the closing of the cracks caused by the prestressing, only slight changes of the modal frequencies were detected before the yielding of reinforcement. Similar conclusions are reported in the works by Capozucca [10] and Di Evangelista et al [11]. Negligible variations of modal frequencies are also reported in [12] for beams prestressed by external tendons and tested with impact hammer tests.…”
Section: Introductionsupporting
confidence: 89%
“…The possibility to detect prestress losses from variations of modal frequencies was investigated also in the paper by Saiidi et al [5] who concluded that the variations of frequencies induced by changes in the prestress in practical ranges are too small to allow a reliable estimation of the prestress losses. Similar conclusions are reported in references [7], [8] and [9] where the variations of the modal frequencies with corrosion are experimentally assessed for prestressed concrete beams. In all these studies very small variations of the modal frequencies are reported for low to medium level of corrosion induced cracking of the concrete.…”
Section: Introductionsupporting
confidence: 88%